High-efficiency perovskite–polymer bulk heterostructure light-emitting diodes. Issue 12 (December 2018) - Zhao, Baodan; Bai, Sai; Kim, Vincent; Lamboll, Robin; Shivanna, Ravichandran; Auras, Florian; Richter, Johannes; Yang, Le; Dai, Linjie; Alsari, Mejd; She, Xiao-Jian; Liang, Lusheng; et al.
Abstract Perovskite-based optoelectronic devices are gaining much attention owing to their remarkable performance and low processing cost, particularly for solar cells. However, for perovskite light-emitting diodes, non-radiative charge recombination has limited the electroluminescence efficiency. Here we demonstrate perovskite–polymer bulk heterostructure light-emitting diodes exhibiting external quantum efficiencies of up to 20.1% (at current densities of 0.1–1 mA cm−2 ). The light-emitting diode emissive layer comprises quasi-two-dimensional and three-dimensional (2D/3D) perovskites and an insulating polymer. Photogenerated excitations migrate from quasi-2D to lower-energy sites within 1 ps, followed by radiative bimolecular recombination in the 3D regions. From near-unity external photoluminescence quantum efficiencies and transient kinetics of the emissive layer with and without charge-transport contacts, we find non-radiative recombination pathways to be effectively eliminated, consistent with optical models giving near 100% internal quantum efficiencies. Although the device brightness and stability (T50 = 46 h in air at peak external quantum efficiency) require further improvement, our results indicate the significant potential of perovskite-based photon sources. Near-infrared perovskite–polymer light-emitting diodes (LEDs) with external quantum efficiencies of up to 20.1% are reported.